2018
DOI: 10.1002/slct.201800730
|View full text |Cite
|
Sign up to set email alerts
|

Electrodeposited MnCO3 as a High Performance Electrode Material for Supercapacitor

Abstract: MnCO3 as an electrode material for supercapacitor is slowly gaining momentum. So far, wet chemical methods have been used to synthesize MnCO3 for supercapacitor applications. The electrode fabrication of thus prepared MnCO3 requires a certain percentage of conductive additive and binder; both of them do not contribute significantly to the measured capacitance. Herein, we report electrodeposition of MnCO3 and its capacitance properties. MnCO3 has been electrodeposited from an aqueous mixture of MnSO4 and Na3C6H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…The R s and R ct were computed by fitting impedance spectra using an equivalent circuit shown in Figure c. It is well known that poor cycling stability of the electrode material is attributed to instability of the material causing phase change or dissolution during cycling, increase in the internal resistance of the material, etc ,. Owing to the high chemical and structural stability of MGCN, it neither undergone dissolution nor phase change during extended cycling as reflected in Figure a.…”
Section: Resultsmentioning
confidence: 99%
“…The R s and R ct were computed by fitting impedance spectra using an equivalent circuit shown in Figure c. It is well known that poor cycling stability of the electrode material is attributed to instability of the material causing phase change or dissolution during cycling, increase in the internal resistance of the material, etc ,. Owing to the high chemical and structural stability of MGCN, it neither undergone dissolution nor phase change during extended cycling as reflected in Figure a.…”
Section: Resultsmentioning
confidence: 99%
“…[15] The internal resistance (R s ) (the intercept on the x-axis at high-frequency region) value of the MC-10, C-10, and M-10 electrode were 0.86 Ω, 1.03 Ω, and 1.96 Ω, respectively, which were less than previously reported MnCO 3 (R s = 11.25 Ω) and Co(CO 3 ) 0.5 (OH) (R s = 3.73 Ω), demonstrating that MnCO 3 synthesized by microwave-assisted synthetic method had lower R s and needle-like Co(CO 3 ) 0.5 (OH) could reduce R s of unitary MnCO 3 . [31,33] Specifically, orderly fabrication of Co(CO 3 ) 0.5 (OH) had increased pathways for the rapid transport of charge transfer and reduced R ct . Compared with C-10 and M-10 electrodes, the MC-10 electrode had the largest slopes in the low-frequency region, indicating the ion/ electron was more efficient.…”
Section: Resultsmentioning
confidence: 99%
“…P. Vishnu Vardhan et al prepared micron MnCO 3 balls via chemical precipitation and applied them to a supercapacitor whose capacitance was 194 F g À 1 at a specific current of 0.5 A g À 1 . [33] Wang et al prepared CoCO 3 woolen balls through the route of microemulsion, which yielded a specific capacitance of 440 F g À 1 at 1 A g À 1 . [34] Leng et al reported single crystal Co(CO 3 ) 0.5 (OH) nanowires with a diameter of ca.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it also exhibits electrochromism . Most importantly, MnCO 3 is studied extensively as an anode material in lithium‐ion batteries, and as an electroactive material in supercapacitors …”
Section: Introductionmentioning
confidence: 99%
“…The capacitance properties of MnCO 3 are studied in either slightly acidic (Na 2 SO 4 , NaClO 4 , Mg(ClO 4 ) 2 ), or alkaline (KOH) electrolytes. The specific capacitance value in the range of 100 to 300 F g −1 reported for MnCO 3 and its composites is believed to arise from both the mechanisms, i. e., adsorption/desorption of ions at the electrode/electrolyte interface resulting in the formation of electric double layer and pseudocapacitance. However, the charge compensation at the Mn sites remains unclear.…”
Section: Introductionmentioning
confidence: 99%